Detection of Anaplasma marginale and A. phagocytophilum in Bovine Peripheral Blood Samples by Duplex Real-Time Reverse Transcriptase PCR Assay - Reinbold, James B. (American Society for Microbiology (ASM), 2010)
Insufficient diagnostic sensitivity and specificity coupled with the potential for cross-reactivity among closely related Anaplasma species has made the accurate determination of infection status problematic. A method for the development of simplex and duplex real-time quantitative reverse transcriptase PCR (qRT-PCR) assays for the detection of A. marginale and A. phagocytophilum 16S rRNA in plasma-free bovine peripheral blood samples is described. The duplex assay was able to detect as few as 100 copies of 16S rRNA of both A. marginale and A. phagocytophilum in the same reaction. The ratio of 16S rRNA to 16S DNA copies for A. marginale was determined to be 117.9:1 (95% confidence interval [95% CI], 100.7:1, 135.2:1). Therefore, the detection limit is the minimum infective unit of one A. marginale bacterium. The duplex assay detected nonequivalent molar ratios as high as 100-fold. Additionally, the duplex assay and a competitive enzyme-linked immunosorbent assay (cELISA) were used to screen 237 samples collected from herds in which anaplasmosis was endemic. When the cELISA was evaluated by the results of the qRT-PCR, its sensitivity and specificity for the detection of A. marginale infection were found to be 65.2% (95% CI, 55.3%, 75.1%) and 97.3% (95% CI, 94.7%, 99.9%), respectively. A. phagocytophilum infection was not detected in the samples analyzed. One- and two-way receiver operator characteristic curves were constructed in order to recommend the optimum negative cutoff value for the cELISA. Percentages of inhibition of 20 and 15.3% were recommended for the one- and two-way curves, respectively. In conclusion, the duplex real-time qRT-PCR assay is a highly sensitive and specific diagnostic tool for the accurate and precise detection of A. marginale and A. phagocytophilum infections in cattle.